An isolated site of calciphilous lichens in the Kujawy region - Ceynowa-Giełdon, Mirosława; Adamska, Edyta; Kamiński, Dariusz (Ecological Questions, 2017)
The paper presents a list of lichen species occurring in three quarries and on mine dumps located within the dust emission impact zone of the cement plant “Kujawy”. The species occur in the lowlands far from their natural localities on limestone rocks in southern Poland. The study area is therefore a valuable habitat island for epilithic and epigeic species of calciphilous lichens in central Poland. Particularly noteworthy are taxa characteristic of natural limestone rocks found in mountain areas of Poland: Verrucaria calciseda, Verrucaria nigroumbrina V. obfuscans and V. polysticta, as well as nine species from the Polish Red List of Lichens: Bacidia rubella, Caloplaca cf. cerina, Enchylium coccophorum, Endocarpon pusillum, Heppia adglutinata, Lempholema chalazanum, Goidanichia ambrosiana, Thelidium incavatum and Th. papulare.